2023
DOI: 10.1007/s11230-023-10093-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated characterisation of nine species of the Schistorchiinae (Trematoda: Apocreadiidae) from Indo-Pacific fishes: two new species, a new genus, and a resurrected but ‘cryptic’ genus

Lori Magro,
Scott C. Cutmore,
Maite Carrasson
et al.

Abstract: We report nine species of the Schistorchiinae Yamaguti, 1942 (Apocreadiidae Skrjabin, 1942) from Indo-Pacific marine fishes. Molecular data (ITS2 and 28S rDNA and cox1 mtDNA) are provided for all species and the genus-level classification of the subfamily is revised. For Schistorchis Lühe, 1906, we report the type-species Sch. carneus Lühe, 1906 and Sch. skrjabini Parukhin, 1963. For Sphinteristomum Oshmarin, Mamaev & Parukhin, 1961 we report the type-species, Sph. acollum Oshmarin, Mamaev & Parukhin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…acutum at 56-65 base positions (12.5-14.5%) in the cox1 dataset, a difference consistent with the recognition of closely related but distinct species for a range of trematode families in the IWP (e.g. Cutmore et al, 2021Cutmore et al, , 2023Huston et al, 2021;Bray et al, 2023;Magro et al, 2023). Further, for Sch.…”
Section: Trematode Identification Over Geographical Rangesupporting
confidence: 71%
“…acutum at 56-65 base positions (12.5-14.5%) in the cox1 dataset, a difference consistent with the recognition of closely related but distinct species for a range of trematode families in the IWP (e.g. Cutmore et al, 2021Cutmore et al, , 2023Huston et al, 2021;Bray et al, 2023;Magro et al, 2023). Further, for Sch.…”
Section: Trematode Identification Over Geographical Rangesupporting
confidence: 71%
“…Based on these studies, the few genetic differences observed between these two sets of sequences, with eight nucleotides over the 28S rDNA (3781 bp) and five nucleotides over the 5.8S and ITS2 (456 bp), led us to identify these specimens as S. cribbi . However, recent studies on Apocreadiidae and Bivesiculidae [ 19 , 37 ] showed that different species for which COI sequence data demonstrated substantial differences all had identical 28S sequences for corresponding specimens. They also showed that for these families, ITS2 and 28S are poor markers for closely related species.…”
Section: Discussionmentioning
confidence: 99%